NATO's European Allies
XI, 310 p.
Keywords: The question of burden sharing has always been important in NATO with an acute relevance today as the US will cut its defence budget over a ten-year period and is no longer automatically willing to lead military operations. This volume considers Europe's role in political force for the future exploring eight European case studies.